LEADERSHIP TRANSFORMATION THROUGH LANGUAGE LEARNING: STRATEGIES AND CHALLENGES: STRATEGIES AND CHALLENGES - Satriah Satriah; M Bambang Purwanto; Anggra Prima (Asosiasi Prodi Manajemen Administrasi Pendidikan Indonesia (APMAPI), 2025)
This study investigates how language learning contributes to leadership transformation among students in higher education. In an increasingly global and multilingual environment, leadership is no longer defined solely by technical competence or formal authority, but also by the ability to communicate effectively, influence others, and manage social interactions. Using a descriptive qualitative approach, this study explores how participation in language learning activities shapes students’ communication practices, leadership behaviors, and social roles within group settings. The participants were 50 students from three diploma programs who had completed courses in Indonesian and English. Data were collected through classroom observations, semi-structured interviews, reflective journals, and documentation of speaking tasks and group discussions. The findings show that language learning enhances leadership communication through increased verbal initiative, more precise message delivery, improved persuasive ability, greater involvement in group decision-making, and higher communication confidence. The study also identifies learning strategies that foster leadership capacity, including group discussions, oral presentations, role-play activities, collaborative projects, and reflective writing. However, several barriers were identified that limit leadership transformation, including fear of making mistakes, limited vocabulary, low self-confidence, cultural inhibition, and unequal participation in groups. Overall, the study concludes that language learning provides a powerful social and communicative space for developing leadership, although its impact depends on both individual and contextual factors.